THE IMPLEMENTATION OF DEMONSTRATION METHOD TOWARD STUDENT LEARNING OUTCOMES IN BASIC PHYSICS II - Azizahwati Azizahwati; Widya Laila; Riri Nasirly (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2018)
This study was aimed to describe the basic physics II learning result of students of Industrial Engineering of Pelalawan Institute of Technology on the electicity material. The subject in this study were the second semester students of Industrial Engineering of Pelalawan Institute of Technology academic year 2017/2018. The instrument which was used to collect the data was the test given after the implementation of the demonstration method. The data was analyzed by using descriptive analysis technique which include student's mastery level. The results of data analysis showed that student learning outcomes were categorized good. The Implementation of demonstration method can improve student learning outcomes on the concept of electricity.